PENGARUH MEREK, KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PERALATAN OLAHRAGA TENIS MEJA OKE SPORT DI KECAMATAN WONOSARI - Muhammad Rifai Kurnia; Djumali Djumali; Istiqomah Istiqomah (Jurnal Bisnis dan Ekonomi, 2017)
This study examined the influence of brand, product quality and promotion to purchasing decisions for sport equipments tennis table at Oke Sport in Wonosari district. The population in this study are all the consumers of Oke Sport in Wonosari district, which the number of population is not known exactly with a sample 100 respondents. Data collection techniques in this study using observations, interviews, questionnaires, and literature. Data analysis techniques in the study is using multiple linear regression, t test, F test, the coefficient of determination. The results of this study show that: 1) Simultaneously variables brand, quality products and promotional influence on purchase decisions at Oke Sport in Wonosari district. 2) Partially variables brand, quality products and promotional influence on purchase decisions at Okay Sport in Wonosari district. Keywords: Brand, Product Quality, Promotion, Purchase Decision.